Optimal handing-back point in mobile data offloading - Zhang, Da (2013)
For vehicular users, mobile data offloading through WiFi has proven its feasibility in reducing the data burden on the cellular networks. By delaying the data request for a while before resorting to the cellular network, the vehicular user can utilize the opportunistically available WiFi connections during the delay to serve its request An important question here is: how long should the user wait for the offloading? Delaying a longer period brings more potential offloading opportunities (i.e. offloaded data volume), but makes the user more and more impatient Furthermore, if no satisfactory amount of data can be offloaded through WiFi during the delay period, the user would think the delay is worthless and lose his enthusiasm in such offloading service. How to find the best time to hand-back the data transfer to the cellular networks from the offloading status, to achieve the optimal trade-off between the offloaded data volume and user satisfaction, is the focus of this paper. We propose a model based on semi-Markov process to accurately predict the potential future offloaded volume. The user satisfaction is modeled as a satisfaction function of the delay period. Then a series of algorithms are proposed to find the optimal handing-back time from offloading. Through extensive simulations and numerical results, our scheme shows its high effectiveness and flexibility.